RIGHT TO RESPECT FOR PRIVATE AND FAMILY LIFE AND PUBLIC SERVICE: PRACTICE OF THE EUROPEAN COURT OF HUMAN RIGHTS - Fomina L.Yu. (Scientific Journal of Pedagogy and Economics, 2020)
The article studies the application of Article 8 of the Convention for the Protection of Human Rights and Fundamental Freedoms, which guarantees the right to respect for private and family life, to the professional activities of civil servants. To summarize and analyze the practice of the European Court of Human Rights in this domain, a dialectical method of cognition was used, as well as such scientific methods as logical, formal legal and other methods, provided that in general the systematic approach was observed. The two approaches to the analysis of interference with private and family life in connection with professional activities: one is based on reasons and the other one – on consequences, were studied. It was concluded that restricting this right in relation to civil servants is admissible if there is a relevant law, a legitimate goal, the need for a democratic society. The correlation of the right to respect for private and family life of civil servants and the right to freely express your opinion guaranteed to everyone was analyzed. It was concluded that it is necessary to search in each case for a fair balance of these rights, taking into account both the interests of society and individuals.